2018
DOI: 10.3389/fendo.2018.00647
|View full text |Cite
|
Sign up to set email alerts
|

The Orexin-A-Regulated Akt/mTOR Pathway Promotes Cell Proliferation Through Inhibiting Apoptosis in Pancreatic Cancer Cells

Abstract: The orexin-A and its receptors are associated with many physiological processes in peripheral organs and the central nervous system and play important roles in a series of human diseases, including narcolepsy, obesity, and drug addiction. Increasing evidence has indicated high expression of orexin-A and OX1 receptor (OX1R) in malignant tumors, suggesting that the stimulation of OX1R might be essential for tumorigenesis. Here, we attempted to clarify the correlation between orexin-A expression and malignancy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
2
16
0
2
Order By: Relevance
“…Data are also contrasting for pancreatic ductal cancer and prostate carcinoma. One study reported that OR1 signaling promotes cell proliferation in pancreatic ductal cancer cells [ 133 ], whereas another study indicated that both agonism (OXA) and antagonism (almorexant) of OR1 exert an antitumoral proapoptotic effect on pancreatic ductal cancer in vitro and in vivo [ 134 ]. On the other hand, OR1 was found to be overexpressed and to mediate apoptosis in advanced prostate cancer with a neuroendocrine differentiation [ 135 ].…”
Section: Orexin Cancer and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Data are also contrasting for pancreatic ductal cancer and prostate carcinoma. One study reported that OR1 signaling promotes cell proliferation in pancreatic ductal cancer cells [ 133 ], whereas another study indicated that both agonism (OXA) and antagonism (almorexant) of OR1 exert an antitumoral proapoptotic effect on pancreatic ductal cancer in vitro and in vivo [ 134 ]. On the other hand, OR1 was found to be overexpressed and to mediate apoptosis in advanced prostate cancer with a neuroendocrine differentiation [ 135 ].…”
Section: Orexin Cancer and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Кроме того, обработка орексином А предотвращает апоптоз клеткок PANC1, тогда как ингибирование OX1R приводит к апоптозу путем регулирования уровней экспрессии в клетках проапоптотических белков Bcl-2, каспазы-9 и c-myc. Авторы считают, что стимуляция рецептора OX1R может быть важна для регуляции онкогенеза при раке поджелудочной железы и является потенциальной мишенью для лечения пациентов с данным типом рака [49].…”
Section: орексин и апоптоз опухолевых клетокunclassified
“…Importantly, the AKT/ mammalian target of rapamycin (mTOR) is known as one of the most critical pathways in regulating cell development, proliferation, and survival [16]. A further study has indicated that the activation of the AKT/mTOR pathway could enhance cell proliferation in PC cells [17]. Besides, another study suggested that the AKT/mTOR pathway could also impact the survival ability and proliferation of prostate cancer cells [18].…”
Section: Introductionmentioning
confidence: 99%